Bilateral Lumbar Micro-Foraminotomy and Micro-Discectomy with 18 Months Postoperative Follow-Up: A Series of 27 Cases (Journal of National Institute of Neurosciences Bangladesh, 2025)
Background: Bilateral lumbar micro foraminotomy and bilateral micro-discectomy is considered as a gold standard surgical technique for the treatment of patients with lumbar disc hernia (LDH) with lateral recess stenosis (LRS) although various types of treatment are being developed.Objective: This study aimed to investigate the safety and efficacy of bilateral lumbar micro-foraminotomy and bilateral micro-discectomy for the treatment of patients with lumbar disc hernia (LDH).Methodology: This was a retrospective cohort study conducted in the Department of Neurosurgery & Neuro-ICU at Enam Medical College & Hospital, Savar, Dhaka during the period of January 2019 to December 2020. All data were collected from patient files. Data were collected pre-designed data collection sheet.Results: This study shows shows maximum (48.1%) were 41 to 50 years followed by 37.0% were 31 to 40 years and 14.8% were 20 to 30 years.  The average age was 39.66±9.25 years. Majority (77.8%) were male and 22.2% cases were female. The most common levels affected by soft disc prolapse recess stenosis are L4-5 and L5-S1 segments. This study shows the mean Oswestry Disability Index (ODI) were 76.11±12.81 in preoperative and 5.00±7.72 postoperative. The decrease in values has been found to be significant in preoperative and postoperative (P